Uveitis and Immunological Disorders - Pleyer, Uwe (Springer, 2017)
This third volume of "Uveitis and Immunological Disorders" in Essentials in Ophthalmology provides up-to-date, relevant information for the reader. Our knowledge and understanding of immune mechanisms has increased exponentially over the past few years and has expanded to disorders such as diabetic retinopathy and macular degeneration. This volume will provide the ophthalmologist with practical information on how to diagnose and treat these difficult, and in some cases, blinding disorders. In addition, there are important discussions of the mechanisms underlying these conditions, which incorporate the most recent, up-to-date research material available. "Summary for the Clinician" and "Core Messages" sections enhance the value of each chapter.